2022
DOI: 10.3390/su14148935
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Different Types of Stainless Steel in PBS Solution

Abstract: Anodic and spontaneous corrosion of different types of stainless steel (AISI 304L, AISI 316L and 2205 DSS) in phosphate-buffered saline solution (PBS, pH = 7.4) at 37 °C (i.e., in simulated physiological solution in the human body) were examined using open circuit potential measurements, linear and cyclic polarization, and electrochemical impedance spectroscopy methods. After the anodic and spontaneous corrosion, the surface of the tested samples was investigated by light and scanning electron microscopy (SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…The obtained results prove the excellent corrosion resistance of the tested biomaterials in environments containing chlorides, which can be proposed for the production of long-term implants. Compared to conventional steel biomaterials, the Ti–13Zr–13Nb alloy, both before and after anodizing, shows exceptional electrochemical properties in PBS solution [ 42 ]. An anodic behavior study of different types of stainless steel in PBS solution revealed that drastically lower breakdown potential (E bd ) values were observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained results prove the excellent corrosion resistance of the tested biomaterials in environments containing chlorides, which can be proposed for the production of long-term implants. Compared to conventional steel biomaterials, the Ti–13Zr–13Nb alloy, both before and after anodizing, shows exceptional electrochemical properties in PBS solution [ 42 ]. An anodic behavior study of different types of stainless steel in PBS solution revealed that drastically lower breakdown potential (E bd ) values were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The surface zeta potential for the non-anodized and anodized Ti–13Zr–13Nb alloy was measured in aqueous electrolytes with different ionic strengths. The following solutions were applied: KCl (0.001 mol L −1 ) as the background electrolyte, PBS (0.001 mol L −l and 0.01 mol L −l ) [ 42 ] and artificial blood (0.01 mol L −l ) [ 43 ] in a wide pH range from over 3 to 9 at 37(2) °C. The pH of these aqueous electrolytes was adjusted with 0.05 mol L −1 HCl and 0.05 mol L −l NaOH, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corrosion resistance of austenitic stainless steels depends on the presence of alloying elements that enhance the stability of the passive film and the absence of those that diminish it. As mentioned in [2], the superior corrosion resistance of austenitic stainless steels can be attributed to the formation of a chromium oxide-hydroxide enriched passive layer, with a thickness ranging from 0.5 nm to 5 nm, when exposed to oxygen. This passive layer exhibits self-healing properties [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 92%
“…Also, its cost can be considered low compared to other resistant materials 3 . These characteristics make this material a usual option in manufacturing surgical devices, such as prostheses, bone fixation, syringes, medical scissors, tweezers, and scalpels [4][5][6] . Its corrosion resistance is mainly associated with the formation of a thin passive film of oxide on the steel surface.…”
Section: Introductionmentioning
confidence: 99%